SISTEM INFORMASI ADMINISTRASI BERBASIS WEB PADA BALAI LATIHAN KERJA INDUSTRI (BLKI) SINGOSARI - Suhermanto, Ari; Rahmawati, Linda Suvi (DINAMIKA DOTCOM, 2013)
Use of information technology has been implemented in almost every institution . It is certainly an impact on the agency as well as for the outsiders . And is a medium that has the potential to be a disseminator of information quickly and effectively.BLKI Singosari is one of the exercises that work to keep track of Information Technology . This technological advancement they use to disseminate information considered useful for the community as well as the media to promote the institution to be more known by the public.However , not a few people who have difficulties in asking for an explanation and description of the institutions. So also in registering at the agency . People who are outside the city , the province and outside the island have difficulty in registering to participate in the course at the Training Center.This study aims to develop a web -based administrative information systems as a medium of information and communication dynamic and user friendly . This information system is expected to be the media in registering and questions posed society .Â Key Words : System, information, administration, web